2015
DOI: 10.1016/j.neuroimage.2015.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Venous cerebral blood volume increase during voluntary locomotion reflects cardiovascular changes

Abstract: Understanding how changes in the cardiovascular system contribute to cerebral blood flow (CBF) and volume (CBV) increases is critical for interpreting hemodynamic signals. Here we investigated how systemic cardiovascular changes affect the cortical hemodynamic response during voluntary locomotion. In the mouse, voluntary locomotion drives an increase in cortical CBF and arterial CBV that is localized to the forelimb/hindlimb representation in the somatosensory cortex, as well as a diffuse venous CBV increase. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
66
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 30 publications
(70 citation statements)
references
References 103 publications
(160 reference statements)
4
66
0
Order By: Relevance
“…Mice rapidly (usually within one session) acclimate to head-fixation, and learn to ‘operate’ the treadmill. After acclimation, resting heart rates in head-fixed mice are comparable to those from recorded telemetrically from mice in their home cage (Gehrmann et al, 2000, Huo et al, 2015b) (Fig. 10), indicating that that head fixation after acclimation is not stressful.…”
Section: Introductionmentioning
confidence: 53%
See 4 more Smart Citations
“…Mice rapidly (usually within one session) acclimate to head-fixation, and learn to ‘operate’ the treadmill. After acclimation, resting heart rates in head-fixed mice are comparable to those from recorded telemetrically from mice in their home cage (Gehrmann et al, 2000, Huo et al, 2015b) (Fig. 10), indicating that that head fixation after acclimation is not stressful.…”
Section: Introductionmentioning
confidence: 53%
“…10), indicating that that head fixation after acclimation is not stressful. In our hands, the pattern of evoked hemodynamic signals are stable up to 10 months of continuous imaging (Huo et al, 2015a, 2015b), which would not be the case if the animals were stressed. Many other groups have used head-fixed rodents, and have shown that they can perform complex, cognitively demanding tasks (Harvey et al, 2009; Komiyama et al, 2010; Mayrhofer et al, 2013; Mehta, 2007; Smear et al, 2011) that use memory or discrimination of stimuli at very high levels, which would not be possible if the animals were excessively stressed.…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations